Guidance and counseling services for reducing youth private social anxiety - Zikra Zikra; Alizamar Alizamar; Afdal Afdal; Miftahul Fikri; Indah Sukmawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2019)
One of the problems faced by juvenile inmates is excessive fear experienced when interacting with new people when they are free to undergo a sentence or also called social anxiety, which requires guidance and counseling services. Guidance and counseling services are one strategy that can be used in alleviating social anxiety faced by prisoners. This article discusses counseling and guidance services that can be done to help alleviate social anxiety of juvenile inmates, which includes Social Anxiety for adolescent inmates and counseling and guidance services, including individual counseling services, group counseling, group counseling. With this service can be given optimal service to adolescent inmates in alleviating the problems faced.